Can AI Improve Public Health Communication? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Artificial intelligence (AI) is no longer the stuff of science fiction. It is rapidly transforming industries, and healthcare is no exception. From diagnosti...
Keywords: AI in Public Health; Improve; Public; Health; Artificial Intelligence; Healthcare; Diagnostics